Parental/grandparental education involvement and adolescents’ learning engagement: a moderated mediation model - Xiang, Xiaoqing; Huang, Xiaofeng; Zhao, Mengyue; Wang, Jing; Shao, Qian (Frontiers in Psychology, 2025)
Parental and grandparental involvement are associated with students’ educational success. However, few studies have explored the different effects of parental and grandparent education involvement on students’ academic performance. This study constructed a hypothetical model of parental/grandparental education involvement and adolescents’ learning engagement, with personal growth initiative as the mediating variable and self-education expectation as the moderating variable, to investigate how parental/grandparental education involvement influences learning engagement. A total of 822 adolescents from middle schools in China participated in the study. The results revealed that parental/grandparental education involvement significantly and positively affected adolescents’ learning engagement. In the context of parental education involvement, the most important factor in promoting learning engagement is emotional leisure. In the context of grandparental education involvement, the most important factor in promoting learning engagement is academic support. Furthermore, personal growth initiative mediated the relationship of parental and grandparental education involvement, respectively. The relationship between parental/grandparental educational involvement and learning engagement was moderated by self-education expectation. However, the interaction effect between self-education expectation and education involvement (emotional leisure, teaching rules, academic support, life care) to predict learning engagement is different between parents and grandparents. For the situation where parents directly raise their children, the interaction term (emotional leisure/teaching rules/academic support × self-education expectation) significantly predicted learning engagement, indicating that self-education expectation moderated the direct effect of emotional leisure, teaching rules, academic support on learning engagement. For the situation where grandparents providing caregiving for grandchildren, only the interaction term emotional leisure × self-education expectation significantly predicted learning engagement, indicating that self-education expectation moderated the direct effect of emotional leisure on learning engagement. The objective of this study was to provide further empirical evidence regarding the discrepancies in the mechanisms by which parental/grandparental education involvement affects adolescents’ learning engagement, and to offer further insights into the promotion of learning engagement among adolescents.